Colorism's impact on the experiences of Black/White multiracial women at predominately White institutions. Issue 174 (5th November 2021) - Harris, Shauna
Abstract: This article provides context for understanding how colorism shapes the identity and lived experiences of multiracial women in college and how higher education institutions can create inclusive and supportive environments for racially mixed students on their campus.